Docosahexaenoic Acid Supplementation is Not Anti- Inflammatory in Adipose Tissue of Healthy Obese Postmenopausal Women - Peter R. Holt; José O Alemán; Jeanne M Walker; Caroline S Jiang; Yupu Liang; Joel Correa de Rosa; Dilip D. Giri; Neil M. Iyengar; Ginger L. Milne; Clifford A Hudis; Jan L Breslow (International Journal of Nutrition, 2017)
Adipose tissue inflammation is associated with obesity comorbidities. Reducing such inflammation may ameliorate these comorbidities. n-3 fatty acids have been reported to have anti-inflammatory properties in obesity, which may modulate this inflammatory state. In the current study a 1 gram per day oral supplement of the n-3 fatty acid docosahexaenoic acid (DHA) was administered for 12 weeks to 10 grade 12 obese postmenopausal women and markers of adipose tissue and systemic inflammation measured and compared before and after supplementation. DHA administration resulted in approximately a doubling of plasma and red cell phospholipid and adipose tissue DHA content but no change in systemic markers of inflammation, such as circulating C-reactive protein (CRP) or interleukins (IL) 6, 8 and 10 (IL-6, IL-8, IL-10). DHA supplementation did not alter the adipose tissue marker of inflammation crown-like structure density nor did it affect any gene expression pathways, including anti-inflammatory, hypoxic and lipid metabolism pathways. The obese postmenopausal women studied were otherwise healthy, which leads us to suggest that in such women DHA supplementation is not an effective means for reducing adipose tissue or systemic inflammation. Further testing is warranted to determine if n-3 fatty acids may ameliorate inflammation in other, perhaps less healthy, populations of obese individuals.
Keywords: n-3 fatty acids